Variable Speed Across Dimensions of Ability in the Joint Model for Responses and Response Times - Zhan, Peida; Jiao, Hong; Man, Kaiwen; Wang, Wen-Chung; He, Keren (Frontiers in Psychology, 2021)
Working speed as a latent variable reflects a respondent’s efficiency to apply a specific skill or a piece of knowledge to solve a problem. In this study, the common assumption of many response time models is relaxed in which respondents work with a constant speed across all test items. It is more likely that respondents work with different speed levels across items, in specific when these items measure different dimensions of ability in a multidimensional test. Multiple speed factors are used to model the speed process by allowing speed to vary across different domains of ability. A joint model for multidimensional abilities and multifactor speed is proposed. Real response time data are analyzed with an exploratory factor analysis as an example to uncover the complex structure of working speed. The feasibility of the proposed model is examined using simulation data. An empirical example with responses and response times is presented to illustrate the proposed model’s applicability and rationality.